Environmental damage assessment due to traditional mining on local scale in the Wungkal Hills, Yogyakarta-Indonesia - Nugraha Febri Ramadhan; Totok Gunawan; Tjahyo Nugroho Adji (Brawijaya University, 2020)
Environmental damage due to mining activities has now become an international issue as its regional and global assessments are widely reported from various mining commodities. Nevertheless, only a few studies have published environmental damage on detailed and local scales. This research was designed to assess the environmental damage induced by traditional mining in the Wungkal Hills, Yogyakarta on these scales by a descriptive exploratory method and quantitative measurement in the field. The mining commodity is clay, which is used as the raw material of bricks and tiles. The observed parameters included abiotic, biotic, and cultural components. The level of damage to abiotic and biotic components due to traditional mining fell into the category of critically damaged. It is attributable to faulty mining procedures that do not incorporate ecological aspects. Changes in landscape, slope, the height of excavation cliff, and the absence of vegetation lead to physical damages by extreme erosion and trigger landslides. Culturally, there was no negative impact on society. Lack of ecological understanding underlays public ignorance of the damage that the traditional mining activities had caused. In the study area, the environmental damages were critical both on detailed and local scales. Reclamation and revegetation based on the agroforestry concept are recommended for the restoration of post-mining land productivity